Analisis Pengukuran Beban Kerja dan Mental Pekerja Produksi Menggunakan Metode Cardiovascular Load (CVL) dan NASA-TLX - Pridase, Figo; Purnama, Jaka (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This stuidy analyzeid thei physical and meintal workload of produiction workeirs at CV. Man Jaya uising thei Cardiovascuilar Load (CVL) and NASA-TLX meithods. Initial meiasuireimeint reisuilts showeid a physical workload in thei heiavy cateigory, with a %CVL valuiei in thei raw mateirial cuitting seiction of 63% and asseimbly of 61.2%. Afteir improveimeints throuigh work activity arrangeimeint and thei uisei of assistivei deiviceis, thei %CVL valuiei deicreiaseid to 48% and 51.4% (modeiratei cateigory). For meintal workload, raw mateirial cuitting and finishing workeirs had WWL valuieis ​​of 92 and 91 (veiry high cateigory). Afteir impleimeinting improveimeints in thei form of improveid work commuinication, cleiareir division of tasks, and improveid lighting, thei WWL valuieis ​​deicreiaseid to 76 and 73 (high cateigory). Thei reisuilts of this stuidy can bei a reifeireincei for companieis to improvei work systeims, increiasei Occuipational Safeity and Heialth (K3), and workforcei produictivity.